2022
DOI: 10.3389/fmicb.2022.757084
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of Yellow Fever Viruses Isolated From Non-human Primates in Brazil With Distinct Genomic Landscapes

Abstract: Since the beginning of the XXI Century, the yellow fever virus (YFV) has been cyclically spreading from the Amazon basin to Brazil’s South and Southeast regions, culminating in an unprecedented outbreak that started in 2016. In this work, we studied four YFV isolated from non-human primates obtained during outbreaks in the states of Rio Grande do Sul in 2008 (PR4408), Goiás (GO05), and Espírito Santo (ES-504) in 2017, and Rio de Janeiro (RJ 155) in 2019. These isolates have genomic differences mainly distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…We selected two final antibodies (MBL-YFV-01 and MBL-YFV-02) that did not compete with each other and neutralized 100% of YFV-ES504 at < 125 ng/mL, then assessed their capacity to neutralize three additional primary isolates from Brazil (YFV-4408-1E, YFV-RJ155, and YFV-GO09) (Table 2). These strains were chosen because they were isolated during different outbreaks ( 10 ). YFV-4408-1E was isolated from a YFV-infected howler monkey in 2008 in Rio Grande do Sul state.…”
Section: Resultsmentioning
confidence: 99%
“…We selected two final antibodies (MBL-YFV-01 and MBL-YFV-02) that did not compete with each other and neutralized 100% of YFV-ES504 at < 125 ng/mL, then assessed their capacity to neutralize three additional primary isolates from Brazil (YFV-4408-1E, YFV-RJ155, and YFV-GO09) (Table 2). These strains were chosen because they were isolated during different outbreaks ( 10 ). YFV-4408-1E was isolated from a YFV-infected howler monkey in 2008 in Rio Grande do Sul state.…”
Section: Resultsmentioning
confidence: 99%
“…The plaque phenotype assay was conducted as described elsewhere [ 45 ]. In summary, Vero cells seeded at 40,000 cells/cm 2 were infected with 10 PFU, 20 PFU, and 40 PFU of each virus.…”
Section: Methodsmentioning
confidence: 99%
“…The cell medium was discarded, and the inocula were adsorbed in the cell monolayer for 1 h. After that, the viral suspension was discarded, the appropriate cell medium was added to the monolayer, and the cells were incubated for 5 days. An aliquot of cell supernatant was collected every 24 h and titrated by plaque assay [ 45 ]. The viral titers were transformed in log 10 and plotted in a dispersion graph for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Yellow fever virus (YFV) is transmitted by the Aeges aegytpi mosquito causing Yellow Fever and while vaccination is available, the virus is continuing to spread to areas of the world where vaccination is not prevalent [ 126 ]. YFV is an enveloped virus with a positive-sense, single-stranded RNA genome.…”
Section: Surface Tlr Associated Virus Interactionsmentioning
confidence: 99%
“…YFV is an enveloped virus with a positive-sense, single-stranded RNA genome. Three structural proteins are encoded by YFV including capsid (C), membrane (prM/M), and envelope (E) along with 7 non-structural proteins [ 126 ]. Modhiran et al identified that NS1 from several Flaviviridae , including YFV, induced the secretion of IL-6 and that this response was likely mediated by TLR4 in PBMCs ( Figure 4 ) [ 107 ].…”
Section: Surface Tlr Associated Virus Interactionsmentioning
confidence: 99%